Own mate value and relative importance of a potential mate's qualities - Tadinac, Meri (Array, 2007)
The aim of this study was to test the hypotheses that individual's mate preferences are in accordance with his/her age, own position on the characteristic especially relevant for the opposite sex (physical attractiveness in females and income in males), and own mate value. The questionnaire, requesting various biographical data and ratings of characteristics of a potential mate regarding their importance or desirability, was posted on the internet and completed by 2648 participants. Women with higher levels of self-perceived physical attractiveness gave higher ratings of importance of a potential partner’ s characteristics, while men with higher income rated potential mate’ s qualities as more important than men with lower income. Participants from high mate value group proved to be choosier, rating majority of characteristics as more important than low mate value group did. Adults of both sexes rated several characteristics as more important compared to very young and older participants, suggesting that people raise their expectations from a potential mate while in their reproductive period.